1981
DOI: 10.1007/bf01317338
|View full text |Cite
|
Sign up to set email alerts
|

Replication of poliovirus and measles virus in cultures of human lymphoblastoid and of burkitt lymphoma cell lines

Abstract: Poliovirus type 1 replicated in 4 different human lymphoblastoid cell lines (LBL) transformed in vitro by EBV virus or isolated from cases of mononucleosis. Maximum virus titers were reached 2--4 days after inoculation. There was a decrease in percentage of viable cells in the infected cultures but a considerable fraction of cells was not destroyed by virus replication. A persistent low grade replication of virus was observed and demonstrable during 56 days after inoculation in one LBL cell line. Presumably a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…These observations confirm what was previously shown for nonrecombinant MV-infected Vero cells (2) and contrast with the results of two studies (16,17) which observed severe actin disruption during MV infection of a human lung cell line. We have confirmed that MVeGFP infection of Vero cells causes no disruption of the actin cytoskeleton (data not shown).…”
Section: Measles Virus (Mv) Is a Morbillivirus Which Belongs To Thecontrasting
confidence: 57%
See 2 more Smart Citations
“…These observations confirm what was previously shown for nonrecombinant MV-infected Vero cells (2) and contrast with the results of two studies (16,17) which observed severe actin disruption during MV infection of a human lung cell line. We have confirmed that MVeGFP infection of Vero cells causes no disruption of the actin cytoskeleton (data not shown).…”
Section: Measles Virus (Mv) Is a Morbillivirus Which Belongs To Thecontrasting
confidence: 57%
“…One group has reported a striking decrease in the overall number of actin bundles in human fibroblasts infected with MV. They also show a similar disruption upon infection with other Paramyxoviridae (16,17). Contrary to this, a second group has not been able to demonstrate alterations to the actin cytoskeleton in MV-infected Vero cells (2).…”
Section: Measles Virus (Mv) Is a Morbillivirus Which Belongs To Thementioning
confidence: 79%
See 1 more Smart Citation
“…Several cell lines derived from hematopoetic tissues, BL lines included, have been reported to be resistant to poliovirus infection (30,31). Northern blot analyses for hPVR mRNA in RNAs of 12 BL cell lines were negative (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that certain cell lines of the hematopoetic lineage cannot be infected with poliovirus (30,31). Most likely, these cells do not express hPVR polypeptides.…”
Section: Cloning Of the 5ј-region Of The Hpvrmentioning
confidence: 99%